PENGARUH INSENTIF TERHADAP DISIPLIN PEGAWAI PADA DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN BIMA - Sa’ban Nurfadli; Muhammad Ali (MANAJEMEN DEWANTARA, 2020)
The purpose of this study was to determine and analyze the effect ofincentives on employee discipline at the Office of Housing and Settlementsof Bima Regency. The type of research used is associative, with a sampleof 68 respondents. The sampling technique used was purposive sampling.The research instrument used was a questionnaire with a Likert scalemeasurement. Data collection techniques by questionnaire, observationand documentation. Data analysis methods used were validity test,reliability test, simple linear regression, coeficient correlation, coeficientdetermination and t test (two part). The results of this study conclude thatincentives have a significant influence on employee discipline asevidenced by the t test value of 9,429 and Sig 0,000. The degree ofinfluence of incentives on employee discipline at Bima Regency Housingand Settlement Service Office is strong.Kata Kunci: Incentives, Employee Discipline